2007
DOI: 10.1007/s10526-007-9099-8
|View full text |Cite
|
Sign up to set email alerts
|

Establishment potential of the predatory mirid Dicyphus hesperus in northern Europe

Abstract: The predatory mirid Dicyphus hesperus Knight (Hemiptera: Miridae) is native to North America. The species has been used for the control of glasshouse whitefly on aubergine in the Netherlands, and is currently being evaluated for continued and wider release in Europe. Field and laboratory studies were conducted on a population collected from southern California, USA, to assess the cold tolerance and potential for outdoor establishment under prevailing northern European climates. The supercooling points (whole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Effect of temperature on rate of development The effect of temperature on development was determined using a method described by Hart et al (2002b) and Hatherley et al (2008) in similar studies on non-native species with potential as biocontrol agents in Europe. Fifty newly moulted adult mirids were placed on each of seven tobacco plants in separate ventilated containers at 23°C, 16:8 LD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of temperature on rate of development The effect of temperature on development was determined using a method described by Hart et al (2002b) and Hatherley et al (2008) in similar studies on non-native species with potential as biocontrol agents in Europe. Fifty newly moulted adult mirids were placed on each of seven tobacco plants in separate ventilated containers at 23°C, 16:8 LD.…”
Section: Methodsmentioning
confidence: 99%
“…Against this background, this paper investigates the cold tolerance of N. tenuis as part of an assessment of its establishment potential in cool temperate climates that occur throughout northern Europe. In a wider context, the data will be used to further examine the relationship between the laboratory survival at 5°C and winter field survival as part of the ERA of non-native biocontrol agents (Hatherley et al 2005(Hatherley et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Bartlett (1974) reported that only 50 % of C. montrouzieri adults survived an exposure of -5.5°C for 12 h. Besides, all C. montrouzieri adults in our study had died by day 24 when exposed to 5°C, indicating its susceptibility to chilling injury due to above-zero cold temperatures. Hatherley et al (2005) reported a strong positive correlation between maximum field survival and survival at 5°C in the laboratory for several arthropod biological control agents and this trend has been confirmed by subsequent studies (Hatherly et al 2008;Hughes et al 2009). When applying the relationship between LTime 50 at 5°C and field survival calculated by Hatherly et al (2005) to our dataset, it can be predicted that C. montrouzieri would not persist longer than 40 days in the field in western European winters and that the ladybird can be classified in the low risk category ).…”
Section: Food Sourcementioning
confidence: 77%
“…The study of a candidate biocontrol agent's establishment potential is considered to be one of the key elements of an ERA procedure (van Lenteren et al 2006;Bale 2011;Ehlers 2011). The methodology developed by Hart et al (2002a) and used in several subsequent studies (Tullett et al 2004;Hatherly et al 2008;Hughes et al 2009;Berkvens et al 2010;Maes et al 2012) to assess cold tolerance of arthropod biological control agents builds on several parameters, including the supercooling point (SCP, the temperature at which the insect's body fluids freeze) and lethal time at 5°C (LTime, time required to kill 50 % of the population at a constant temperature of 5°C).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of comparative ecophysiological data for these species has revealed a strong correlation between indices of laboratory cold hardiness and duration of winter survival in the field (Hatherly et al 2005b). More recent investigations on other species, including the predatory mirid Dicyphus hesperus Knight (Hemiptera: Miridae) (Hatherly et al 2008) has further strengthened this predictive relationship. Unless future studies reveal several 'contradictory species', it would appear that the LTime 50 at 5°C in the laboratory is a reliable predictor of overwintering success.…”
Section: Introductionmentioning
confidence: 94%